2015
DOI: 10.3171/2014.10.jns141610
|View full text |Cite
|
Sign up to set email alerts
|

Adverse radiation effect after stereotactic radiosurgery for brain metastases: incidence, time course, and risk factors

Abstract: abbreviatioNs ARE = adverse radiation effect; AVM = arteriovenous malformation; CI = confidence interval; HR = hazard ratio; PACS = picture archiving and communication system; SRS = stereotactic radiosurgery; UCSF = University of California, San Francisco; WBRT = whole-brain radiation therapy. obJect The authors sought to determine the incidence, time course, and risk factors for overall adverse radiation effect (ARE) and symptomatic ARE after stereotactic radiosurgery (SRS) for brain metastases. methods All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(208 citation statements)
references
References 12 publications
8
184
1
1
Order By: Relevance
“…However, the authors utilized logistic rather than time-dependent competing risks regression [19]. A separate investigation comprising 118 RN events reported that capecitabine delivered within 1 month of SRS was associated with an increased risk of symptomatic RN [5], though this finding was not replicated in our series. A possible explanation for this is that the authors did not perform subset analyses among individual pathologies (specifically breast cancers).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 67%
See 1 more Smart Citation
“…However, the authors utilized logistic rather than time-dependent competing risks regression [19]. A separate investigation comprising 118 RN events reported that capecitabine delivered within 1 month of SRS was associated with an increased risk of symptomatic RN [5], though this finding was not replicated in our series. A possible explanation for this is that the authors did not perform subset analyses among individual pathologies (specifically breast cancers).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 67%
“…However, radiation necrosis (RN) is the primary dose-limiting toxicity following SRS, occurring following 5-10% of treatments [4][5][6]. RN is symptomatic Abstract To investigate late toxicity among patients with newly-diagnosed brain metastases undergoing stereotactic radiosurgery (SRS) with concurrent systemic therapies with or without whole-brain radiation therapy (WBRT).…”
Section: Introductionmentioning
confidence: 99%
“…This is higher than for the iPlan plans that have been our clinical standard prior to introducing the VMAT technique but since Gamma Knife plans typically use a PTV D max >140% we accepted this higher inhomogeneity to reduce the GI. The risk of radiation necrosis following cranial SRS has been reported in several studies 13, 14, 15, 16, 17, 18. More data are needed to determine if the difference in dose distribution between the planning techniques have potential clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-specific clinical considerations for SRS and HF-SRS include life expectancy of a given patient, urgency of other needed systemic treatments for the patient, and whether those therapies, such as chemotherapy, immunotherapy, antibody therapies, or even antibiotics, may be delivered concurrently. Other patient-specific clinical considerations are inherent factors such as hypertension, diabetes, smoking history, vasculitis, and other medical comorbidities that may make a patient more susceptible to toxicity, such as radiation necrosis, 32,33 following SRS.…”
Section: Neurooncologymentioning
confidence: 99%